Competitive Effects of Charter Schools - David N. Figlio; Cassandra M.D. Hart; Krzysztof Karbownik (Center for Economic Studies and ifo Institute (CESifo), 2024)
Using a rich dataset that merges student-level school records with birth records, and leveraging three alternative identification strategies, we explore how increase in access to charter schools in twelve districts in Florida affects students remaining in traditional public schools (TPS). We consistently find that competition stemming from the opening of new charter schools improves reading—but not math—performance and it also decreases absenteeism of students who remain in the TPS. Results are modest in magnitude.
Keywords: H75; I21; I22; I28; 330